EAP needs analysis of medical sciences foundation students at the Center For Foundation Studies (CFS), International Islamic University Malaysia (IIUM) / Marlina Zubairi - Zubairi, Marlina (2014)
The purpose of this current study is to investigate the academic English language needs of medical sciences foundation students at the Center For Foundation Studies, International Islamic University Malaysia. 200 foundation students who would be majoring in Medicine, Dentistry, Pharmacy and Allied Health Sciences programs as well as 20 ESL and Science lecturers were involved in this study. Based on two comprehensive needs analysis approaches - Target Situation Analysis (TSA) and Present Situation Analysis (PSA), data were collected using both the quantitative and qualitative research methods via two sets of questionnaires and semi-structured interviews. The results revealed several important findings. It was found that there were some inconsistencies in perceptions between the lecturers and students in terms of students’ difficulties in listening, reading and writing. The lecturers believed that the students had more problems in these skills than the students themselves. However, despite the mismatch, both students and lecturers agreed that problems concerning grammar and vocabulary expressions are students’ greatest concern in all the four language skills. In addition, it was also found that reading and writing were viewed to be the two most important skills for students to succeed in their academic studies. These findings indicate the significant importance of needs analysis procedure as it could help in the development and review of the EAP course in CFS, HUM. As a result, an effective language curriculum which benefits the students can be offered.